2016
DOI: 10.1182/blood-2015-09-618538
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils, platelets, and inflammatory pathways at the nexus of sickle cell disease pathophysiology

Abstract: Sickle cell disease (SCD) is a severe genetic blood disorder characterized by hemolytic anemia, episodic vaso-occlusion, and progressive organ damage. Current management of the disease remains symptomatic or preventative. Specific treatment targeting major complications such as vaso-occlusion is still lacking. Recent studies have identified various cellular and molecular factors that contribute to the pathophysiology of SCD. Here, we review the role of these elements and discuss the opportunities for therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
353
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 330 publications
(365 citation statements)
references
References 119 publications
6
353
0
6
Order By: Relevance
“…Furthermore, pathway-based analysis of these transcriptomes clusters to signaling cascades known to be pathophysiologically relevant in SCD. 7,11,15,19,26,[33][34][35][36] Our data suggest that the transcriptome classifier is a biomarker that reflects disease severity as evidenced by abnormalities in important pathways that are driven by HbS polymerization and reflect the systemic nature of the complications of SCD. As such, FAIME analyses provide insights into the potential mechanistic and pathophysiological relevance of molecular clusters downstream of the inciting HgS polymerization event in SCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, pathway-based analysis of these transcriptomes clusters to signaling cascades known to be pathophysiologically relevant in SCD. 7,11,15,19,26,[33][34][35][36] Our data suggest that the transcriptome classifier is a biomarker that reflects disease severity as evidenced by abnormalities in important pathways that are driven by HbS polymerization and reflect the systemic nature of the complications of SCD. As such, FAIME analyses provide insights into the potential mechanistic and pathophysiological relevance of molecular clusters downstream of the inciting HgS polymerization event in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Seemingly heterogeneous pathways in porphyrin metabolism, bile secretion, and complement and coagulation cascades along with VEGF signaling and immune-mediated processes have all been shown to be directly relevant to SCD. 7,11,15,19,26,[33][34][35][36] Recently, meta-analysis of 4 published datasets of differentially regulated molecular pathways related to SCD demonstrated near identical pathways to those that are associated with survival in the current work including porphyrin metabolism, complement and coagulation cascades, VEGF signaling, and immune-mediated processes. 15 Another group evaluated differentially regulated genes by both RNAsequencing and conventional gene expression profiling in whole For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…35 Our studies demonstrate that oral administration of a single dose of both hydroxyurea and ARQ 092 efficiently inhibits neutrophil-endothelial cell and neutrophilplatelet interactions in cremaster venules and reduces neutrophil recruitment into the alveoli of TNF-α-challenged SCD mice. Interestingly, survival was improved by hydroxyurea alone or both hydroxyurea and ARQ 092, but not ARQ 092 alone.…”
Section: Discussionmentioning
confidence: 95%
“…35 Our study shows that ARQ 092 reduces the ligand-binding function of αMb2 integrin in stimulated neutrophils isolated from SCD patients. Importantly, we found that ARQ 092 inhibits αMb2 integrin function in neutrophils isolated from SCD mice after oral administration of the inhibitor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation